A sustainability analysis of environmental impact, nutritional quality, and price among six popular diets - Yacoub Bach, Lara; Jana, Bethany E.; Adaeze Egwatu, Chisom Freda; Orndorff, Corey Jane; Alanakrih, Rinad; Okoro, Joy; Gahl, Megan K. (Frontiers in Sustainable Food Systems, 2023)
This paper is an extension of Masset et al.’s (2014) analysis of individual food items commonly found in the French diet and their environmental, nutritional, and financial impact. In the analysis, Masset et al. (2014) propose a relative sustainability score to compare food items and define which are the most sustainable, finding that meat and dairy products are the most detrimental to the environment. Using this proposed relative sustainability score, we compare the Mediterranean, paleo, ketogenic, vegetarian, and vegan diets, along with the World Health Organization dietary guidelines in order to evaluate which diets are most sustainable. We collected environmental, nutritional, and price data on individual food items and generated weekly dietary intakes. Using an online meal-prep program, we organized one week’s worth of meals for each diet consisting of 2000 kilocalories per day and then calculated an estimate of greenhouse gas emissions, eutrophication, land use, water withdrawals, nutritional quality, and affordability, ultimately calculating an overall relative sustainability score based on metric averages to compare diets. Our model indicates that vegan, Mediterranean, and vegetarian diets are the most sustainable across all metrics while meat-heavy diets, such as the ketogenic diet, have the greatest negative environmental impact. A diet based on the World Health Organization’s dietary guidelines performed poorly with regards to affordability, environmental impacts, and nutritional quality. Diets with higher nutritional quality included the vegan, paleo, and Mediterranean diets. Diets that eliminate meat were the cheapest both by total cost and by cost per gram of food. The diets with the highest overall sustainability score share a common characteristic: they all suggest that consumers committed to sustainability should prioritize “plant-forward” diets. In contrast, diets rich in meat and animal products perform poorly overall but especially in terms of environmental sustainability.